THEME IN SOCIAL (WITH THESIS) NOVELS OF PIRIMKUL KADIROV - Erhan GİRAY (Fırat University, 2019)
Pirimkul Kadirov who is one of the leading authors of modern Uzbek literature, started authorship with stories. In following periods he became famous with his novels. The Üç Kök (1958), Kara Gözler (1966) and Elmas Kemer (1976) novels of Kadirov who wrote 6 novels have social subjects. In Üç Kök novel the problems faced in universities and people using their authority for their benefits, in Kara Gözler novel, the negative effects of kolhoz and sovhoz system on community and in Elmas Kemer the harm given to environment by urbanization are emphasized. Kadirov who well analyzed the socio-cultural problems of his period reflected what he wanted to explain to his novels. He focused especially on history and history consciousness themes in order to prevent Uzbek community, which stayed under Soviet regime pressure for long years, to split from its past. Again it is possible to mention about communism and Leninism in background of his novels as a result of Soviet government policies. Although love theme which was used in all three novels stayed in the background, it is used to explain women-men relations.